Editorial - Núñez, María Teresa Teresa Esteban (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Classroom research is the consequence of reflective teaching. To this respect, Richards and Lockhart (1994,1 in Bailey, Curtis and Nunan, 2001) say that “teachers and student teachers collect data about teaching, examine their attitudes, beliefs assumptions, and teaching practices, and use the information obtained as a basis for critical reflection about teaching” (p.p 37).